HUBUNGAN SPIRITUALITAS TERHADAP DEPRESI PADA LANSIA YANG TIDAK MEMILIKI PASANGAN HIDUP - Hartiningsih, Sri Nur; Setyorini, Andri; Oktavianto, Eka (MEDIA ILMU KESEHATAN, 2020)
Background: Depression disorders are often found in patients with their prevalence throughout life, in women 10% -25% and in men 5% - 12% and around 15% of depressed sufferers make suicide attempts. The prevalence of depression, regarding more than 20% of elderly people living in community areas, 25% of elderly people are in the hospital and 40% of elderly residents living in nursing homes. Symptoms of depression in the elderly are changes in sleep patterns, decreased appetite and weight, changes in mood. Overcoming the problem of depression in the elderly can be done with a spiritual approach, which seeks to maintain harmony or harmony with the outside world, struggle to answer or gain strength when facing depression, emotional stress, physical illness or death.Objective: Know the relationship between spirituality and depression in elderly people who do not have a partner.Methods: non-experimental quantitative research type with descriptive correlational research design. This research was conducted at the Budi Luhur PSTW Hall, with a sample of 60 respondentsResults: The results of this study use Pearson-product moment correlation with the results of the correlation coefficient of - 0.027 and at a significant level of 0.083 this indicates that the p value <0.05.Conclusion: These results can be concluded that there is a relationship between spirituality and depression in the elderly who do not have a partner in the Balai PSTW Unit Budhi Luhur Yogyakarta Keywords: Depression, elderly, spirituality